The Drosophila homolog of human tumor suppressor TSC-22 promotes cellular growth, proliferation, and survival. - Wu, X.; Yamada-Mabuchi, M.; Morris, E.J.; Tanwar, P.S.; Dobens, L.; Gluderer, S.; Khan, S.; Cao, J.; Stocker, H.; Hafen, E.; Dyson, N.J.; Raftery, L.A. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
TSC22D1, which encodes transforming growth factor beta-stimulated clone 22 (TSC-22), is thought to be a tumor suppressor because its expression is lost in many glioblastoma, salivary gland, and prostate cancers. TSC-22 is the founding member of the TSC-22/DIP/Bun family of leucine zipper transcription factors; its functions have not been investigated in a multicellular environment. Genetic studies in the model organism Drosophila melanogaster often provide fundamental insights into mechanisms disrupted in carcinogenesis, because of the strong evolutionary conservation of molecular mechanisms between flies and humans. Whereas humans and mice have four TSC-22 domain genes with numerous isoforms, Drosophila has only one TSC-22 domain gene, bunched (bun), which encodes both large and small protein isoforms. Surprisingly, Drosophila Bun proteins promote cellular growth and proliferation in ovarian follicle cells. Loss of both large isoforms has the strongest phenotypes, including increased apoptosis. Cultured S2 cells depleted for large Bun isoforms show increased apoptosis and less frequent cell division, with decreased cell size. Altogether, these data indicate that Drosophila TSC-22/DIP/Bun proteins are necessary for cellular growth, proliferation, and survival both in culture and in an epithelial context. Previous work demonstrated that bun prevents recruitment of epithelial cells to a migratory fate and, thus, maintains epithelial organization. We speculate that reduced TSC22D1 expression generally reduces cellular fitness and only contributes to carcinogenesis in specific tissue environments.